Antimicrobial Activity of Ozone against Pathogenic Oral Microorganisms on Different Denture Base Resins - Hayran, Yeliz; DENİZ, ŞULE TUĞBA; DENİZ, ŞULE TUĞBA; Aydin, Ali (My University, 2019)
The present study aimed to evaluate the antimicrobial effect of gaseous ozone against specific oral pathogens on denture base resins. 1080 round samples were prepared (10mm-diameter, 2mm-thickness). Candida albicans, Streptococcus mutans, Streptococcus gordonii, and Aggregatibacter actinomycetemcomitans, polyamide-Deflex, heat-cured polymethyl-methacrylate (PMMA)-QC-20, and cold-cured-PMMA-Meliodent. The doses and durations: 25, 50 and 100 mu g/ml, 5, 10, 20, 30 minutes. For Cell viability (CV) MTT was used. 100 mu g/ml was most effective dose for C. albicans, S .gordonii, and A. actinomycetemcomitans were in heat-cured-PMMA and polyamide for S.mutans. For polyamide, lowest CV was 43% in S.mutans and A.actinomycetemcomitans. CV of heat-cure and cold-cure PMMA were 31% and 32% in S.gordonii, respectively. CV was similar for all resins and durations in S.mutans and A.actinomycetemcomitans and for polyamide for C.albicans and for heat-cure PMMA for S.gordonii. 30-min ozone application killed 80% of all microorganisms in all resins except for C.albicans in polyamide (65% cell death) and cold-cure PMMA (57% cell death). Optimal dose/duration combination was 100 mu g/ml-10 min. Gaseous ozone can be considered as an effective cleansing agent for denture base resins.